PENGARUH DISIPLIN KERJA DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN DI PT.BPR SARI SEDANA SANGLAH DENPASAR - Ni Komang Ayu Ega Pratiwi; A.A. Putu Agung; Ni Putu Nita Anggraini (VALUES, 2022)
Performance is a person's willingness to carry out an activity and perfect it according to his responsibilities so that the goals set by the company can be achieved. Factors that can affect employee performance are work discipline and career development. This research was conducted to determine the effect of work discipline and career development on employee performance at PT. BPR Sari Sedana. This research was conducted at PT.BPR Sari Sedana which is located at Jl. Diponegoro No. 252 Sanglah Denpasar. The object of this research is about Work Discipline and Career Development on Employee Performance at PT. BPR Sari Sedana Sanglah Denpasar. The population in this study were all employees of PT. BPR Sari Sedana, totaling 40 people. Determination of the sample in this study using a saturated sample is a sampling technique when all members of the population are used as samples. namely 40 respondents for the sample test. The results of this study indicate that work discipline has a positive and significant effect on employee performance at PT. BPR Sari Sedana Sanglah Denpasar, and career development have a positive and significant effect on employee performance at PT. BPR Sari Sedana Sanglah Denpasar.